The Balanced Scorecard and Strategy Map - Eni Nurhaedin; Bima Chandra Widiya Utama; Rachmad Widodo (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Measuring future executive performance requires a comprehensive measure that includes 4 (four) perspectives, namely: the financial perspective provides an overview of financial goals, the customer perspective provides an overview of market segments, the internal business process perspective provides an overview of achieving company goals, learning, and growth perspective. The application of the balanced scorecard method to measure the performance of PT Segara Tours & Travel can be applied to measure the performance of all elements or parts of PT Segara Tours & Travel. Travel and Company scorecards can be used as a reference for performance appraisals which contain performance measures that have been mapped into responsible departments at PT Segara Tours & Travel.